Dimethyl fumarate-related immune and transcriptional signature is associated with clinical response in multiple sclerosis-treated patients - Sánchez-Sanz, Alicia; García-Martín, Santiago; Sabín-Muñoz, Julia; Moreno-Torres, Irene; Elvira, Víctor; Al-Shahrour, Fátima; García-Grande, Aranzazu; Ramil, Elvira; Rodríguez-De la Fuente, Ofir; Brea-Álvarez, Beatriz; García-Hernández, Ruth; García-Merino, Antonio; et al. (Frontiers in Immunology, 2023)
Background and objective: Dimethyl fumarate (DMF) is an immunomodulatory drug approved for the therapy of multiple sclerosis (MS). The identification of response biomarkers to DMF is a necessity in the clinical practice. With this aim, we studied the immunophenotypic and transcriptomic changes produced by DMF in peripheral blood mononuclear cells (PBMCs) and its association with clinical response. Material and Methods: PBMCs were obtained from 22 RRMS patients at baseline and 12 months of DMF treatment. Lymphocyte and monocyte subsets, and gene expression were assessed by flow cytometry and next-generation RNA sequencing, respectively. Clinical response was evaluated using the composite measure “no evidence of disease activity” NEDA-3 or “evidence of disease activity” EDA-3 at 2 years, classifying patients into responders (n=15) or non-responders (n=7), respectively. Results: In the whole cohort, DMF produced a decrease in effector (TEM) and central (TCM) memory T cells in both the CD4+ and CD8+ compartments, followed by an increase in CD4+ naïve T cells. Responder patients presented a greater decrease in TEM lymphocytes. In addition, responder patients showed an increase in NK cells and were resistant to the decrease in the intermediate monocytes shown by non-responders. Responder patients also presented differences in 3 subpopulations (NK bright, NK dim and CD8 TCM) at baseline and 4 subpopulations (intermediate monocytes, regulatory T cells, CD4 TCM and CD4 TEMRA) at 12 months. DMF induced a mild transcriptional effect, with only 328 differentially expressed genes (DEGs) after 12 months of treatment. The overall effect was a downregulation of pro-inflammatory genes, chemokines, and activators of the NF-kB pathway. At baseline, no DEGs were found between responders and non-responders. During DMF treatment a differential transcriptomic response was observed, with responders presenting a higher number of DEGs (902 genes) compared to non-responders (189 genes). Conclusions: Responder patients to DMF exhibit differences in monocyte and lymphocyte subpopulations and a distinguishable transcriptomic response compared to non-responders that should be further studied for the validation of biomarkers of treatment response to DMF.